Estudo da dinâmica da solução do solo para o manejo da fertirrigação por gotejamento na cultura do pimentão - Santoro, Bruno de Lima (2011)
Among various systems, the drip irrigation has been increasingly used, mainly because of its greater efficiency in water use. This work aimed to study the dynamics of soil solution, characterizing the distribution and storage of nutrients in the soil solution, and their absorption by pepper through the management of drip fertigation with two flows rates. The experiment was conducted in a greenhouse located in the Department of Agricultural Science, Unitau. The soil of study is an Oxisol Yellow, medium texture. The crop cycle lasted 120 days. From the readings of TDR probes were possible to estimate water content and soil solution concentration. Thus, the distribution of soil solution was monitored and counted in layers of 0,1m to 0,6 m. The evaluation of root system showed that the treatment of 4 L h-1 had an area of 69,31 cm2, while the treatment of 2 L h-1 had an area of 45,21 cm2. The productivity was 0,19 kg m-2 and 0,27 kg m-2 for 2 Lh-1 and 4 L h-1, respectively, what reinforces the results of nutrients distribution and root system development. It was found that for treatment with the flow rate of 2 L h-1 there was a trend of nutrient loss by percolation, increasing possible contamination of groundwater. The dripper with a flow rate of 4 L h-1 was more efficient at distributing and storing water and nutrients in a soil profile, which improved crop yield.